2018
DOI: 10.1007/s13730-018-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

A case of fatal osteolytic hypercalcemia complicated with IgG4-related ophthalmic disease leading to renal failure

Abstract: A 40-year-old male was hospitalized with renal impairment and severe hypercalcemia. His concentration of serum IgG4 was high, but serum whole PTH, 1-25(OH) vitamin D3 and PTHrP were not elevated. Computed tomography showed swelling of the bilateral lacrimal glands and systemic lymphadenopathy. The histological findings of lacrimal gland biopsy fulfilled the diagnostic criteria of IgG4-related ophthalmic disease (IgG4ROD). Bone scintigraphy showed increased ectopic uptake in the stomach, heart, lungs, and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…The remaining 2 cases 11,15 were similar to our patient, who had non-PTH-related hypercalcemia and the serum PTH levels were decreased. Tranah et al 15 reported a patient diagnosed with IgG4-RD involving thyroid gland, submandibular gland, and lymph nodes, and had a good response to high-dose corticosteroid treatment.…”
Section: Non-pth-related Hypercalcemia In Igg4-rdsupporting
confidence: 81%
See 3 more Smart Citations
“…The remaining 2 cases 11,15 were similar to our patient, who had non-PTH-related hypercalcemia and the serum PTH levels were decreased. Tranah et al 15 reported a patient diagnosed with IgG4-RD involving thyroid gland, submandibular gland, and lymph nodes, and had a good response to high-dose corticosteroid treatment.…”
Section: Non-pth-related Hypercalcemia In Igg4-rdsupporting
confidence: 81%
“…7,10 Hypercalcemia occurring in patients with IgG4-RD is not common. A literature review showed that only 5 definitely [11][12][13][14][15] (including 1 conference abstract 15 ) and 2 possible (not biopsied) IgG4-RD 16,17 associated hypercalcemia had been reported (Table 1). According to the literature, the pathogenesis of IgG4-RD-associated hypercalcemia can be divided into parathyroid hormone (PTH)-related and non-PTH-related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low calcium can lead to circumoral or peripheral paranesthesia, tetany, carpopedal spasm, laryngospasm, and ECG changes from long QT interval to VT arrest [1,2]. While high calcium can cause fatigue, polyuria, polydipsia, nephrolithiasis, peptic ulcer disease, altered mental status, gait instability [3][4][5], myalgia, arthralgia, abdominal pain [4], rare submandibular gland atrophy and sialolithiasis, metastatic pulmonary calcification [6,7], sometimes even inducing acute kidney injury or acute pancreatitis [8][9][10][11][12][13], or being life-threatening [14,15]. The parathyroid gland is an adjacent organ of the thyroid.…”
Section: Introductionmentioning
confidence: 99%